2012
DOI: 10.1016/j.chembiol.2012.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Morphobase, an Encyclopedic Cell Morphology Database, and Its Use for Drug Target Identification

Abstract: Visual observation is a powerful approach for screening bioactive compounds that can facilitate the discovery of attractive druggable targets following their chemicobiological validation. So far, many high-content approaches, using sophisticated imaging technology and bioinformatics, have been developed. In our study, we aimed to develop a simpler method that focuses on intact cell images because we found that dynamic changes in morphology are informative, often reflecting the mechanism of action of a drug. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 33 publications
3
79
0
Order By: Relevance
“…Structural genomics and systems pharmacology greatly benefit from innovations in molecular informatics (50,51). We implemented and experimentally validated a unique method for ligand-based target prediction that extends the capabilities of related approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Structural genomics and systems pharmacology greatly benefit from innovations in molecular informatics (50,51). We implemented and experimentally validated a unique method for ligand-based target prediction that extends the capabilities of related approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Discriminant analysis determines the distance from each point of the data set to the multivariate mean of each class and then assigns the point to the closest class (33). Essentially, discrimi- 12.57 (16) No antibiotic treatment (control) None None nant analysis is divided into two steps: (i) to build (i.e., "train") a model (i.e., classifier) using Raman spectra of cultures exposed to antibiotics of known class assignments, and (ii) to classify (i.e., predict the class of) a new Raman spectrum of an antibiotic-exposed culture based on the distance to the multivariate mean of the closest class. Two class assignment schemes were used with discriminant analysis to achieve the following two distinct objectives.…”
Section: Determination Of Mics E Coli Mach1 Cells (Invitrogen Lifementioning
confidence: 99%
“…Principal component analysis (PCA) of metabolomic profiles, obtained using high-performance liquid chromatography-mass spectrometry (HPLC-MS) data, revealed that the mechanism of action of Radix Tinosporae was similar to that of rifampin and norfloxacin (14). Techniques for multiparameter imaging-based phenotypic profiling rely on high-throughput fluorescence microscopy (15) or morphological analysis (16) and have shown great promise in drug discovery research (2,7). For example, bright-field cell imaging coupled with nuclear staining was used to construct a library of morphological profiles for cancer cells exposed to 54 anticancer drugs with known molecular targets (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The high-content cell morphology database Morphobase utilizes similarity in chemical-genetic phenotype of cancer cell lines treated with small molecules for rapid target identification. 26 …”
Section: Methods In Target Identification and Elucidation Of Mechanmentioning
confidence: 99%